DEVELOPMENT OF A POCKET BOOK (ARABIC-ENGLISH-INDONESIAN) TO IMPROVE SPEAKING SKILLS AT MADRASAH ALIYAH BAHRUL ULUM MALANG - Afkhoriyatul Hilmi (International Conference on Social and Islamic Studies, 2021)
This pocket book (Arabic-English-Indonesian) was developed for students of Madrasah Aliyah class X. The development of this book was carried out as a solution, because there are still few textbooks that focus on maharah kalam that are applicable and can be directly applied in everyday life. In addition, some of the exercises in the textbook do not match the skills learned. The large and colorless book size makes students feel bored and bored while studying. The objectives of this research are (1) to develop a pocket book (Arabic-English-Indonesian) to improve speaking skills. (2) To find out the effectiveness of the books that have been developed and applied to class X Madrasah Aliyah Bahrul Ulum Malang students. This research uses Borg and Gall Research and Development (R&D) research which has been modified from ten steps into six main steps, namely, (1) Needs analysis, (2) Planning, (3) Product development, (4) Validation of material experts. and media, (5) Revision, (6) Field trial, and produce the final product. (1) This book consists of six main materials with the development of themes related to daily activities and is equipped with pictures of conversations that are adapted to the themes being studied, and there is a quick response code (QR-Code) which contains videos of interesting conversational practices. The design of this book is made in color and not too big, so students can easily carry it and can use it. Wherever and whenever. Instruments of data collection were obtained through interviews with Arabic teachers, field observations conducted by researchers, and questionnaires given to students. As a research sample, the researcher tested the validity of the book to the tenth grade students of Madrasah Aliyah Bahrul Ulum Malang. (2) Based on the average assessment results from the material validation test with the presentation of the material validation results 92%, while for media validation 73% and learning practitioners 92%. The results of the assessment show that this book is valid for learning maharah kalam for class X Madrasah Aliyah.